Clinical Features and Treatment Outcomes of Chronic Nonbacterial Osteomyelitis in Children: A Multicenter Study in China - LIU Haimei; ZHANG Tianyu; MA Le; ZHANG Zhiyong; XU Meng; ZHANG Tao; XU Hong; TANG Xuemei; YANG Sirui; YU Haiguo; SONG Hongmei; SUN Li (Xiehe Yixue Zazhi, 2023)
Objective  To investigate the clinical features and treatment outcomes of chronic non-bacterial osteomyelitis (CNO) from five tertiary pediatric rheumatology services in China and provide possible treatment options for clinicians.  Methods  In this multicenter, retrospective study, pediatric patients diagnosed with CNO in Children's Hospital of Fudan University, Peking Union Medical College Hospital, Children's Hospital of Nanjing Medical University, Children's Hospital of Chongqing Medical University and the First Hospital of Jilin University from March 2014 to August 2022 were included. According to the treatment plan, the patients were divided into nonsteroidal anti-inflammatory drugs (NSAID) group, traditional disease modifying anti-rheumatic drugs (DMARD) group, tumor necrosis factor inhibitor (TNF-i) group, bisphosphonate group, and bisphosphonate+TNF-i group, and physician global assessment score was used to evaluate the efficacy.  Results  Retrospective data analysis showed that the disease was more common in boy sthan girls(31 vs. 27), and the average age at onset of symptoms was 8.5±3.4 years, the mean age of diagnosis was 9.8±3.2 years, and the Median follow-up was 10.9(5.0, 30.1) months. A total of 46 cases (79.3%) were diagnosed in the last 3 years. Bone pain and / or arthralgia was the predominant symptom in 54(93.1%) patients followed by fever in 31(53.4%) patients. Raised inflammatory markers (ESR and CRP) were present in 87.9% and 77.6% of the patients. The most frequently affected bones were lower limb bones, including 42 cases of femur and 41 cases of tibia; 3 patients had compression fractures of the vertebrae at the time of diagnosis. Bone biopsy was conducted in 33 cases, and subacute or chronic osteomyelitis manifested with inflammatory cells infiltration were detected. The remission rate was not statistically different between treatment groups (P=0.562), with the remission rate at 11 months in the bisphosphonate+TNF-i group being 60.0%, 55.6% and 33.3% in the NSAID and DMARD groups respectively; 66.7% and 52.4% in the NSAID and TNF-i groups respectively at 12 months. A total of 40 patients were followed up for ≥6 months, with the remission rate of 81.3%.  Conclusions  Our multicenter study describes the features and outcomes of CNO patients in China. The characteristics of CNO children from multiple centers in China were lack of specificity. Bone pain and/or arthralgia were the main clinical symptoms, accompanied by fever, normal white blood cells, and raised inflammatory markers (CRP and/or ESR). Although anti-inflammatory treatment regimens were different, the efficacy of the treatment groups was similar. Anti-inflammatory therapy is currently the first choice.